Present scenario and problem confrontation of rooftop gardening and its efficacy in ambient environment reclamation in Khulna City of Bangladesh - Sheel, Manabika; Ahmed, M Bashir; Khan, S A Kamal Uddin; Islam, M Matiul (Fundamental and Applied Agriculture, 2019)
In the urban area there is scarce space for planting trees and cultivating agri- cultural plants. Rooftop gardening might be an alternative to overcome this land scarcity. The present study analyzes the scenario of rooftop gardening, its problem confrontation and its effects on the surroundings. Nirala and Son- adanga area of Khulna city of Bangladesh were purposively selected for the study from where a total of 60 rooftop gardens were randomly selected for face-to-face interview with a pre-tested interview schedule during the period of 15 March to 20 April, 2018. Results showed that majority of the rooftop gardeners belonged to the group of old age (40%), undergrad and above level of education (61.6%) and small family size (55%) with high annual income (41.7%). Majority of them had low experience (40%), but high knowledge (76.7%) on rooftop gardening. Besides, 58.3% respondents had no organiza- tional participation along with seldom extension contact (66.7%) and seldom cosmopoliteness (81.7%). More than half of the respondents (65%) had small size (≤1000 ft2) roof area suitable for gardening. The rooftop gardeners earned very poor economic benefit from the garden compared to bearing large expenditure for it. Most of the respondents preferred rooftop garden as a hobby (98.3%) and aesthetics (90%). Again, 51.7% respondents considered it as an aspect of ecological balance. Vegetables (16.6%) and flowers (12.5%) were the most dominating plants in the study area for rooftop gardens. Main intercultural operations included irrigation, weeding, training/pruning and control of insects and diseases. Commonly faced insects were ant, mealy bug and green leaf hopper with the diseases of die back, viral disease, leaf curling and leaf scorching. Common fertilizers used in the study area were cow dung, compost, urea, muriate of potash and sesame cake. Excessive heat (91.7%), lack of proper nourishment (87.1%) and roof load (72.9%) were the most severe problems. Among the 9 selected characteristics only age of the respondents showed significant positive relationship with problem confrontation. Besides, weather parameters showed positive impacts in case of green roof than empty roof. Thus, the overall results indicate great con- tributions of rooftop gardening in urban areas in terms of environmental reclamation.